Efektivitas Layanan Bimbingan Kelompok dalam Meningkatkan Kegiatan Merespon Pembelajaran - Rizky Andana Pohan; Syaiful Indra (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study aims to determine: a description of the average condition score of activities responding to students in learning before and after treatment guidance services are given; and the effectiveness of group guidance services to improve student response activities in learning. This research uses quantitative methods. This type of research is pre-experimental, using the one group pre-test post-test design. The selection of subjects in this study uses a non-random sampling technique with a purposive sampling method. The subjects of this study were ten people and were treated for six meetings. The instrument used was the Responding scale Rizky Andana Pohan Likert scale model. Data were analyzed using non-parametric statistical techniques using the Wilcoxon Signed Ranks Test with the help of SPSS version 17.00. The research findings show that in general group guidance services are effective in increasing response activities in learning, while specifically this study describes: there are differences in the average score of student response activities before and after group guidance services are provided. Based on the results of this study, it can be concluded that the activities of responding to students in learning can be improved through group guidance services.